Gestão nos processos de patentes: desenvolvimento e implantação do sistema de gestão de patentes na Universidade Federal do Maranhão – UFMA - LIMA, Antonio Jardson dos Santos (2024)
Public university carry out research that results in new products, processes or improvements that can be protected by patents, a property title that allows universities to obtain economic, institutional and social benefits. These titles are managed by the institutions' Technological Innovation Centers (NITs), which monitor the processing of requests and actively maintain them. At the Federal University of Maranhão (UFMA), the management of patent applications, from filing with the National Institute of Industrial Property (INPI) to granting, is carried out manually, which requires more time, attention and coud lead to error. Therefore, the purpose of this study was to develop software with the aim of supporting the management of UFMA's patent processes and thus making the work more efficient and faster. The methodology consists of bibliographical, documentary research and a case study, seeking to obtain data and information related to the UFMA patent application portfolio and the current model of management and control of the processes used in NIT. Based on the results obtained through a quality management tool it was found that UFMA has 172 patents applications, considering those in force; of this total 22 being managed by other co-owner institutions leaving 150 applications for the NIT of UFMA manager. The study also revealed some problems in the sector, the main ones being the time spent and mistakes in processes, the root cause of which is operational management carried out manually. Therefore, the possible functionalities that will be integrated into the software were defined through brainstorming, which will facilitate the work of NIT servers, contributing to minimizing errors, increasing productivity and speeding up management processes.